2019
DOI: 10.1186/s12917-019-1914-9
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity and mode of action of acetone crude leaf extracts of under-investigated Syzygium and Eugenia (Myrtaceae) species on multidrug resistant porcine diarrhoeagenic Escherichia coli

Abstract: Background Diarrhoea, a global economically important disease burden affecting swine and, especially piglets, is commonly caused by infection with entero-toxigenic E. coli (ETEC). Adherence of ETEC to porcine intestinal epithelial cells following infection, is necessary for its pathogenesis. While antimicrobials are commonly given as therapy or as feed additives for prophylaxis against microbial infections, the concern over increased levels of antimicrobial resistance ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 80 publications
2
21
0
2
Order By: Relevance
“…The MIC and MBC results from this experiment showed that the root extract of B. antidysenterica has the ability to inhibit and kill bacteria. The MIC of an extract is regarded as good if the values are less than 0.1 mg/mL, moderate if it is between 0.1 and 0.625 mg/mL and weak when it is above 0.625 mg/mL [40,57]. Based on this, the MIC of 80% hydro-methanolic crude extract of B. antidysenterica was ranged from moderate to weak against the tested bacteria strains.…”
Section: Discussionmentioning
confidence: 99%
“…The MIC and MBC results from this experiment showed that the root extract of B. antidysenterica has the ability to inhibit and kill bacteria. The MIC of an extract is regarded as good if the values are less than 0.1 mg/mL, moderate if it is between 0.1 and 0.625 mg/mL and weak when it is above 0.625 mg/mL [40,57]. Based on this, the MIC of 80% hydro-methanolic crude extract of B. antidysenterica was ranged from moderate to weak against the tested bacteria strains.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, acetone leaf crude extracts of Eugenia zeyheri and Syzygium legatii had excellent antimicrobial activity with MICs varying from 0.04 to 0.23 mg/ml on clinical and reference strains of E. coli. It also reduced the attachment of E. coli to intestinal cells in a Caco-2 cell adhesion assay [15].…”
Section: Introductionmentioning
confidence: 96%
“…The susceptibility of organisms to different antibiotics were tested using the disk diffusion method as described [21,23]. On freshly prepared Mueller Hinton agar and standardized by the method of Famuyide et al [24] and National Committee for Clinical Laboratory Standard (NCCLS) [22] using some selected antibiotics namely: tetracycline (30µg), pefloxacin (10µg), ampiclox (30µg), streptomycin (30µg), gentamicin (10µg), erythromycin (10µg), ciprofloxacin (10µg), amoxicillin (30µg), penicillin G (10µg), septrin (30µg) metronidazole (20 μg/disk) and imipenem (10 μg/disk). For each combination of the antibiotics and the bacterial strains, the experiment was performed in triplicate.…”
Section: Antibiotic Susceptibility Testingmentioning
confidence: 99%